Fascin Expression in Melanocytic Lesions of the Skin - Yíldíz, L.; Kefeli, M.; Aydín, O.; Kandemír, B. (John Libbey Eurotext Ltd, 2009)
Fascin is a globular actin cross-linking protein that is important in carcinogenesis. It shows differential staining in various tumors, dependent on grade and stage. The purpose of this study was to compare fascin expression in benign, dysplastic and malignant (metastatic and nonmetastatic) melanocytic lesions of the skin, and also to investigate the potential role of fascin in their differential diagnosis. Fascin expression was investigated through the immunohistochemistry of paraffin-embedded tissue in 73 cases of melanocytic lesions of the skin, including 20 benign nevi, 12 dysplastic nevi, 4 lentigo malignas, 25 malignant melanomas and 12 metastatic melanomas. The cases were scored on the basis of staining extension (from 0 to 4) and intensity (from 1 to 3), and were assigned a combined score. Fascin expression was present in 19/20 (95%) benign nevi, 8/12 (67%) dysplastic nevi, 1/4 (25%) lentigo malignas, 7/25 (28%) malignant melanomas and 3/12 (25%) metastatic melanomas. There was significantly less frequent expression of fascin in malignant melanoma than in benign nevi (p < 0.001) and dysplastic nevi (p = 0.036). The results of this study indicate that differential fascin expression exists between benign nevi and malignant melanomas. Fascin can therefore serve as a reliable immunohistochemical marker in distinguishing malignant melanomas from melanocytic nevi and dysplastic nevi, and it may be used with histological criteria for differential diagnosis.
Keywords: Differential Diagnosis; Fascin; Malignant Melanoma; Melanocytic Lesion